INTERVENSI KESEHATAN PENCEGAHAN STUNTING PADA IBU HAMIL DI NEGARA BERKEMBANG: REVIEW SISTEMATIS - Chaerin Nabila Fitriyah; Eilien Theodora; Rifka Silmia; Soraya Risanda; Wahyu Sulistiadi (VISIKES: Jurnal Kesehatan Masyarakat, 2019)
Mother's knowledge about nutrition during pregnancy plays a major role in thecase of stunting in infants. Intervention against pregnant women who experiencemalnutrition is very important to prevent stunting in infants who are born. Thisstudy aims to identify interventions that are most widely applied and effective wayto reduce the number of low birth weight infants are potentially stunting. Theliterature is searched on the database PubMed and Cochrane Library withspecific keywords. Article found in a review by PRISMA systematic review, finallyfound 10 journal articles to be analyzed. Search results show the intervention ofmultiple micronutrients is a type of intervention that are most widely used andeffective in improving birth weight babies compared to iron-folate supplementsthe granting and administering of lipid nutrition. However, training health workersabout the intervention of multiple micronutrients when the ANC was stillinadequate and the costs of multiple micronutrients are more expensive thansupplements folic acid. This has become the application of multiplemicronutrients interventions for secondary society down. Multiple micronutrientswas the method of intervention is most effective and need to be promoted as aprimary intervention for pregnant women especially who experience malnutrition.Keywords: Stunting, intervention, expectant mothers, developing countries